Comparison Between (311–312 nm) Narrow Band Ultraviolet-B Phototherapy and (308 nm) Monochromatic Excimer Light Phototherapy in Treatment of Vitiligo: A Histopathological Study - Salah-Eldin, Manal Mohamed; Sami, Nevien Ahmed; Aly, Dalia Gamal-eldin; Hanafy, Noha Sami (Journal of Lasers in Medical Sciences, 2017)
Introduction: Recently, the monochromatic excimer light (MEL) of 308 nm wavelength has shown some advantages in comparison to narrow band ultraviolet B (NB-UVB) for the treatment of vitiligo. To histopathologically compare the early effects of NB-UVB and 308-nm MEL phototherapy on vitiliginous patches using H&E and HMB-45. Methods: Thirty subjects with non-segmental vitiligo lesions were treated twice a week for 6 weeks with 308-nm MEL, while NB-UVB was used to treat lesions contra laterally. Skin biopsies were taken from lesional areas before and after 6 weeks of treatment by either modality. It was prepared for light microscopy and immunohistochemical study (HMB-45). This study was performed as a clinical trial (Trial registration: http://www.pactr.org; Identifier: PACTR201705002279419) Results: All lesions before treatment had labeling index (number of pigmented cells/non-pigmented cells) of 0.0 (0%). After treatment the LI for MEL was 4.2 ± 2.6, while for NB-UVB LI it was 0.3 ± 0.7. MEL showed higher statistical significance regarding increase of basal pigmented cells, and significant decrease in vacuolated keratinocytes and basal membrane thickness than NB-UVB. Conclusion: Although NB-UVB is considered as treatment of choice for vitiligo, MEL is acknowledged as an effective treatment modality for vitiliginous lesions that induces more repigmentation than NB-UVB, and more rapidly, as confirmed by our study.